Analisis Kepuasan Pengguna Website SIAPEL Dalam Pelayanan KTP Elektronik Kota Malang Menggunakan Metode E-Govqual - Modesta Inda Kartikawati; Rizza Muhammad Arief (J-INTECH ( Journal of Information and Technology), 2024)
The implementation of e-government as an innovation in public administration using information technology prompted the Malang City government to launch the SIAPEL website, offering various public services, including electronic ID card (E-KTP) services. Despite facing challenges, such as the absence of formal research on user satisfaction, there is a critical need to evaluate the satisfaction level of E-KTP service users on the SIAPEL website. This study employs the e-govqual method, focusing on dimensions like ease of use, trust, reliability, and citizen support. The research findings indicate that all questionnaire items are valid, normally distributed, and reliable based on validity, normality, and reliability tests. The t-test identifies three significant variables influencing user satisfaction: ease of use, trust, and reliability. Furthermore, through multiple linear regressions and f-tests, it is evident that all variables significantly and positively affect user satisfaction. Overall, the e-govqual method effectively evaluates user satisfaction levels, affirming that all studied variables play a crucial role in determining user satisfaction.